In Search of Medea’s Atypical Motherhood in Euripides’ Medea: Cultural and Historical Perspective - Biswas, Prakash Chandra; Kayoum , Md. Abdul; Rochi, Marzia Rahman (International Journal of Applied Educational Research (IJAER), 2024)
This research aims to highlight the common traits of atypical motherhood portrayed in Euripides’ tragic play, “Medea” focusing on the character of Medea. The study explores the contrast between revenge and motherhood, showcasing how Medea challenges the traditional maternal roles which often emphasize nurturing and protective qualities. Medea challenges these norms and Conventional expectations through her complex and controversial actions by navigating the intricate interplay between love, revenge, and societal norms. The study employs a multidisciplinary approach, incorporating literary analysis, psychoanalytic perspectives, and cultural studies to unravel the layers of Medea’s action. Through a detailed analysis of Medea’s character, the paper examines subtle representations of motherhood, revealing the tensions between maternal instinct and the pursuit of individual agency. Additionally, the research investigates how cultural and historical context of ancient Greece influenced the construction of maternal roles in the play. By delving into the character of Medea, this study contributes to a deeper understanding of the complex dynamics surrounding motherhood within the context of classical Greek literature. Furthermore, it invites reflection on the enduring relevance of these themes in contemporary discussions on gender, power, and societal expectations. Through this exploration, the paper aims to contribute to a nuanced understanding of maternal roles in classical literature and stimulate discourse on the portrayal of atypical motherhood in ancient narratives.